The relationship between marital reminiscence styles and psychological well-being through mediating role of marital quality - Majzoobi, Mohammad Reza; Forstmeier, Simon (Frontiers in Psychology, 2025)
IntroductionMarital relationships are deeply shaped by the memories couples share, as reminiscence plays a pivotal role in fostering emotional connection and intimacy. Investigating how such reminiscence is related to marital quality provides valuable insights into its influence on relational dynamics. Therefore, the purpose of the present study was to examine the relationship between marital reminiscence styles (MRSs) and psychological well-being (PWB) through the mediating role of marital quality.MethodsThis was a descriptive-correlational study. The statistical population included all married people living in Kermanshah, Iran in 2023, among whom a sample of 304 people were selected using convenience sampling method. The measures used in this study were Majzoobi and Forstmeier’s (2025) marital reminiscence styles Questionnaire (MRSQ), Chonody et al.’s (2018) Relationship quality Questionnaire, and Ryff’s PWB Questionnaire. Data were analyzed through Pearson’s correlation coefficient and structural equations modeling (SEM) in SPSS-26 and LISREL-10 software.ResultsThe findings indicated that the hypothesized model had a good fit in the studied sample. MRSs were significantly associated with PWB through marital quality. As such, it was found that obsessive MRS is related negatively to marital quality, which, in turn, related positively to PWB. Moreover, narrative MRS was related positively to marital quality, which, in turn, related positively to PWB.DiscussionThese results underscore the importance of fostering positive MRSs, such as narrative MRS, to enhance marital quality and PWB in marital relationships.